Comparing law : comparative law as reconstruction of collective commitments / Catherine Valcke, University of Toronto. - Valcke, Catherine (ASCL studies in comparative law., 2018)
The enterprise of comparative law is familiar, yet its conceptual whereabouts remain somewhat obscure. Comparing Law: Comparative Law as Reconstruction of Collective Commitments reconstructs comparative law scholarship into a systematic account of comparative law as an autonomous academic discipline. The point of that discipline is neither to harmonize world law, nor to emphasize its cultural diversity, but rather to understand each legal system on its own terms. As the proposed reconstruction exercise involves bridging comparative law and contemporary legal theory, it shows how comparative law and legal theory both stand to benefit from being exposed to each other. At a time when many courses are adding a transnational perspective, Valcke offers a more theoretical, broadened, and refreshed view of comparative law.